Hepatocellular Transplantation for Metabolic Support in Experimental Acute Ischemic Liver Failure in Rats - Kazuyoshi Takeshita; Haruaki Ishibashi; Masayuki Suzuki; Masashi Kodama (Cell Transplantation, 1993)
The function of transplanted hepatocytes in acute ischemic liver failure was studied in an experimental model using rats. Ischemic liver failure was induced by occlusion of the proximal portal vein and hepatic artery immediately following extracorporeal portofemoral venous bypass. All rats were bred in a closed colony. Rats in Group 1 were untreated and served as controls (n = 10). Rats in Group 2 received an intrasplenic transplant of hepatocytes (1 × 107 cells) 48 h before liver ischemia (n = 10). Serum ammonia and blood glucose were measured before, and 1 h after, ischemia. Serum ammonia was significantly higher than normal (Group 1, 930 μg/dL vs < 110 μg/dL) after liver ischemia. On the other hand, serum ammonia in group 2 also was elevated (355 μg/dL), but significantly less so than in Group 1 (p < 0.001). Blood glucose was lower in both groups after liver ischemia, compared to normal (50-100 mg/dL), but it was higher in Group 2 (30 mg/dL) than in Group 1 (14 mg/dL, p < 0.01). Liver histology 1 h after ischemia showed similar degrees of necrosis in the two groups. Transplanted hepatocytes were viable, and clearly identified in the splenic parenchyma after ischemia. Intrasplenic transplanted hepatocytes provide temporary metabolic support of acute ischemic liver failure in rats, as reflected by enhanced ammonia removal and gluconeogenesis.